Cytogenetic finding of simultaneous inversion of chromosome 14 and tetrasomy 8 in a Pediatric B-Lymphoblastic Leukemia-a case report - Kiran Sachwani; Rehab Pasha; Bushra Kaleem; Neelum Mansoor (Molecular Cytogenetics)
Abstract Background Clonal cytogenetic abnormalities in B-lymphoblastic leukemia (B-ALL) include structural and numerical chromosomal alterations, where numerical are the most common aberrations. Inversion 14 [inv(14)] is an infrequent finding in B-ALL, but its prognostic and therapeutic significance has not been previously explored. Case presentation A 13-year-old boy diagnosed as B-ALL on bone marrow aspirate by flow cytometry is presented. Fluorescence in situ hybridization (FISH) for B-ALL panel was reported as normal. Nevertheless, his cytogenetic studies performed on bone marrow showed tetrasomy 8 and a pericentric inversion in chromosome 14. Conclusion Inversion 14 is a rare finding in B-ALL, and its clinical relevance is worthy of further evaluation. The growing number of such cases reported emphasizes that there exists a possibility of a separate cytogenetic subset with diagnostic, prognostic or even therapeutic relevance.